2017
DOI: 10.3389/fpsyt.2017.00161
|View full text |Cite
|
Sign up to set email alerts
|

Malmö Treatment Referral and Intervention Study—High 12-Month Retention Rates in Patients Referred from Syringe Exchange to Methadone or Buprenorphine/Naloxone Treatment

Abstract: BackgroundHeroin dependence is associated with high mortality. Opioid agonist treatment (OAT) with methadone or buprenorphine has strong evidence for treatment of this relapsing condition. In our setting, OAT has been associated with strict and demanding intake procedures, often with requirements of social stability, but also high, approximately 80 percent 12-month retention rates. In a recent randomized controlled trial, we demonstrated high rates of successful rapid referral from a syringe exchange programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…One proposed explanation for the paucity of interventions offered to PWID may be presumed lack of social stability or resources for treatment adherence. However, a Swedish study found parity in 12-month retention rates among MOUD program participants with and without strict social stability requirements [ 25 ]. Another study found homelessness positively predicted MOUD initiation among hospitalized adults seen by an addiction consult service, indicating that hospitalization may be an important opportunity to engage typically harder to reach populations [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…One proposed explanation for the paucity of interventions offered to PWID may be presumed lack of social stability or resources for treatment adherence. However, a Swedish study found parity in 12-month retention rates among MOUD program participants with and without strict social stability requirements [ 25 ]. Another study found homelessness positively predicted MOUD initiation among hospitalized adults seen by an addiction consult service, indicating that hospitalization may be an important opportunity to engage typically harder to reach populations [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a Swedish study found parity in 12-month retention rates among MOUD program participants with and without strict social stability requirements. 24 Another study found homelessness positively predicted MOUD initiation among hospitalized adults seen by an addiction consult service, indicating that hospitalization may be an important opportunity to engage typically harder to reach populations. 25 Insurance status was also likely not the primary barrier in receiving behavioral health services as only 36% of the admitted patients receiving services in that study had private insurance.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously presented a low-threshold procedure for rapidly referring opioid-dependent individuals from a NEP to evidence-based treatment with methadone and buprenorphine [48]. Despite having a high degree of problems due to use of illicit substances, signs of severe psychiatric symptomatology, and social problems, patients were retained in treatment to a high degree at 12-month follow-up [53]. In conclusion, authors have however suggested that patients and staff are not always in agreement with what characterizes efficient OAT [7], that retention and reduction in substance use and other “hard” data only describe part of the truth when it comes to treatment success, and that quality of life measures should be used as part of outcome evaluation [10–12].…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 71 individuals who started OAT, 67 patients (94%) were still in treatment after three months [53]. In-treatment patients had to leave observed toxicology screens twice a week.…”
Section: Methodsmentioning
confidence: 99%